Suplementação de vitamina A em dietas para Kinguios (Carassius auratus) - Fries, Edionei Maico (2014)
Vitamin A is important to the proper development and functioning of the body, appearing in several metabolic functions. This experiment was conducted with aim evaluate to the vitamin A supplementation in diets for Goldfish Carassius auratus. The experimental was completely randomized with six treatments (0, 2.000, 4.000, 8.000, 16.000 and 32.000 IU of vitamin A kg(-1) diet) with four repetitions into 24 experimental cages, with capacity for 150 liters useful volume, made of mesh shading, installed inside a masonry circular tank with a capacity of 25 m(3) of water. 192 fish with an average initial weight of 6.66 +/- 0.57 g and initial length of 7.30 +/- 0.33 cm, feed at 8h, 11h, 14h and 17h at satiety were used. Evaluated the effects on productive performance and intensity of yellow-red coloring of the skin of the fish were. The Linear Response Plateau analysis of weight gain and length total, feed conversion and daily growth rate versus vitamin A requirement estimate showed 2,624, 2,385 and 2,358, 4,381 and 2,866 IU of vitamin A per kg diet, respectively. The data indicated that this vitamin has little or no influence on the intensity of the skin color of the Goldfish.